2006
DOI: 10.1111/j.1471-0528.2006.01068.x
|View full text |Cite
|
Sign up to set email alerts
|

Ovarian reserve tests for predicting fertility outcomes for assisted reproductive technology: the International Systematic Collaboration of Ovarian Reserve Evaluation protocol for a systematic review of ovarian reserve test accuracy

Abstract: Background  The presence of a wide range of tests of ovarian reserve suggests that no single test provides a sufficiently accurate result. Many tests are used without reference to an evidence base. So far, individual studies conducted on these tests are too small to give precise estimates of prognostic accuracy. Objectives  To systematically assess the accuracy of the available tests of ovarian reserve in terms of prediction of fertility outcomes. Search strategy  The search will be conducted using the name of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
30
0
5

Year Published

2007
2007
2019
2019

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 67 publications
(37 citation statements)
references
References 60 publications
2
30
0
5
Order By: Relevance
“…Around 1 % of women will experience premature ovarian failure before 40 years of age. It follows that the women who undergo an earlier menopause, will also experience an earlier loss of fertility, leaving approximately 10 % of women who will have decreased ovarian function in their early to mid 30s [15].…”
Section: Introductionmentioning
confidence: 99%
“…Around 1 % of women will experience premature ovarian failure before 40 years of age. It follows that the women who undergo an earlier menopause, will also experience an earlier loss of fertility, leaving approximately 10 % of women who will have decreased ovarian function in their early to mid 30s [15].…”
Section: Introductionmentioning
confidence: 99%
“…Advanced hormonal assessments (estradiol, inhibin B, anti-M€ ullerian hormone) and ultrasound assessments (antral follicle count, ovarian volume) to assess ovarian reserve [14] may be additionally recommended for couples with unexplained infertility and/or those that are candidates for AR, as the ovarian reserve may be directly associated with the chances of natural conception (albeit within an extended timeframe) as well as with the chances for response to ovarian stimulation.…”
Section: Basic and Extended Infertility Assessments: Pros And Consmentioning
confidence: 99%
“…By ROC analysis, the cutoff value of inhibin B to identify poor responders was found to be 23.75 pg/ml. Seifer et al reported higher cycle cancelation rates and lower pregnancy rates in women with low (\45 pg/ml) day 3 serum inhibin B concentrations [6]. According to the study of Seifer et al, the value of inhibin B of 45 pg/ml was considered as a cutoff to identify poor responders.…”
Section: Roc Curvementioning
confidence: 99%